TEACHING ENGLISH SPEAKING THROUGH STORY TELLING METHOD (A FIELD RESEARCH AT SDN CENGKARENG BARAT 03 PAGI) - Fitriyeni Fitriyeni (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
Abstract The object of this research is to apply storytelling method in teaching English speaking. The research was conducted at the fourth grade SDN Cengkareng Barat 03 Pagi in academic year 2017/2018. In process teaching, writer used theory by Fikriah which describes about procedures of teaching used storytelling method to improved speaking skill. Writer used picture as media and also students experience to learn English speaking. The writer analyses the process of teaching and collecting data through; field research, library research, and internet. There are some difficulties in English speaking that found at SDN Cengkareng Barat 03 pagi, such as students’ vocabulary still less, lack of ideas to tell, and students afraid to speak louder. During process teaching run, there are some advantages of using storytelling method, these was : (1) Improving students’ activeness and imagination in speaking, especially in the implementing or telling a story (2) students brave to speak in front of class to tell the story (3) by practice directly students more understood the material given. Thus, it can be said that storytelling method could improve students’ speaking skill